Ответ:
22 4,14
24 1,0
Объяснение:
22
Х+10 - первый
Х - второй
Х-12+10 - стало у первого
Х-8 - стало у второго
Х-2>х-8 на 1,5
Х-2=1,5(х-8)
Х-2=1,5х-12
Х+1,5х=10
2,5х=10
Х=4 - было у второго
4+10=14 - было у первого
24
(а+7)х=а+7
Х=а+7/а+7
Х=1
(6-а)х=0
Х=0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
22 4,14
24 1,0
Объяснение:
22
Х+10 - первый
Х - второй
Х-12+10 - стало у первого
Х-8 - стало у второго
Х-2>х-8 на 1,5
Х-2=1,5(х-8)
Х-2=1,5х-12
Х+1,5х=10
2,5х=10
Х=4 - было у второго
4+10=14 - было у первого
24
(а+7)х=а+7
Х=а+7/а+7
Х=1
(6-а)х=0
Х=0